2017
DOI: 10.1063/1.5001834
|View full text |Cite
|
Sign up to set email alerts
|

Envelope solitons in three-component degenerate relativistic quantum plasmas

Abstract: The criteria for the formation of envelope solitons and their basic features in a three-component degenerate relativistic quantum plasma (DRQP) system (containing relativistically degenerate electrons, non-degenerate inertial light nuclei, and stationary heavy nuclei) are theoretically investigated. The nonlinear Schrödinger equation is derived by employing the multi-scale perturbation technique. The envelope solitons are found to be associated with the modified ion-acoustic waves in which the inertia (restori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…It is believed that the components of the DQPS are electrons, positively charged heavy ions (e.g., 56 26 Fe [4], 85 37 Rb [5], 96 42 Mo [5]), and positively charged light ions (e.g., 1 1 H [6,7], 4 2 He [8], 12 6 C [9,10]). A number of authors investigated nonlinear waves in DQPS with positively charged heavy and light ions and electrons [11][12][13][14]. The characteristics of DQPS are comprehensively governed by the number density of the plasma species of DQPS, and it has been observed that the electron number density in white dwarfs is in the order of 10 30 cm −3 to 10 39 cm −3 , and even more in neutron stars [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that the components of the DQPS are electrons, positively charged heavy ions (e.g., 56 26 Fe [4], 85 37 Rb [5], 96 42 Mo [5]), and positively charged light ions (e.g., 1 1 H [6,7], 4 2 He [8], 12 6 C [9,10]). A number of authors investigated nonlinear waves in DQPS with positively charged heavy and light ions and electrons [11][12][13][14]. The characteristics of DQPS are comprehensively governed by the number density of the plasma species of DQPS, and it has been observed that the electron number density in white dwarfs is in the order of 10 30 cm −3 to 10 39 cm −3 , and even more in neutron stars [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…for the ultra-relativistic limit [13,14]. The degenerate pressure only depends on the number density of the plasma species but not on their temperature [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst, Alfvén waves (AWs), which are lowfrequency electromagnetic waves, propagate along the direction of the magnetic field. Over several years, the significant characteristics of degenerate quantum plasmas encouraged investigators to examine the propagation of nonlinear waves in different configurations [2][3][4][5][6][7][8][9]. For degenerate quantum plasmas, the de Broglie thermal wavelength of the quantum charged particles is comparable to the characteristic spatial scales of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury et al [19] have reported that the MI of nucleus-acoustic waves (NAWs) in a DQP system and found that the MI growth rate of the unstable NAWs is significantly modified by the number density of nucleus species. Islam et al [20] have studied envelope solitons in three component DQP. However to the best of our knowledge, no attempt has been made to study MI of the IAWs in SG-DQPS.…”
Section: Introductionmentioning
confidence: 99%